catena-Poly[[bis(2-hydroxy-2-phenylacetato-κ(2) O (1),O (2))zinc(II)]-μ-1,2-di-4-pyridylethane-κ(2) N:N′] - Yu, Seung Man (International Union of Crystallography, 2009)
The title compound, [Zn(C(8)H(6)O(3))(2)(C(12)H(12)N(2))](n), consists of [Zn(Hopa)(2)] (H(2)opa = 2-hydroxy-2-phenylacetic acid or mandelic acid) units bridged by 1,2-di-4-pyridylethane (bpe) ligands, forming a polymeric chain developing parallel to the b axis. The bridging bpe ligand is arranged around a twofold axis passing through the middle of the ethane C—C bond. The geometry around the Zn(II) ion is distorted octahedral, constructed by four O atoms from two Hopa(−) ligands and two N atoms from two bridging bpe ligands. O—H⋯O hydrogen bonds link the chains, forming a three-dimensional network.